Diet and social status on Taumako, a Polynesian outlier in the Southeastern Solomon Islands. Issue 4 (18th July 2013) - Kinaston, Rebecca L.; Buckley, Hallie R.; Gray, Andrew
ABSTRACT Stable isotopes (δ13C, δ15N, and δ34S) are used to characterize the diet of the adult individuals (n = 99) interred in the Namu burial ground located on the Polynesian outlier of Taumako (∼300–750 BP). Polynesian outliers are islands on the fringe of Remote Oceania that were inhabited by a back migration of populations from Polynesia during prehistory. As a result of admixture with nearby island communities, little is known about the social structure and social diversity of the prehistoric inhabitants of Taumako. The distribution of prestige grave goods within the Namu cemetery has been used as evidence to support the premise that Taumakoan social structure was stratified like Polynesian societies. Here we test the hypothesis that "wealthy" individuals and males will display isotopic ratios indicative of the consumption of "high status" foods in the Pacific islands such as pork, chicken, sea turtle, and pelagic fish. The isotope results suggest the δ34S values were diagenetically altered, possibly an effect of volcanism. The carbon and nitrogen stable isotope ratios indicate that the diet of all the individuals included a mixture of C3 terrestrial plant foods (likely starchy staples such as yam, taro, and breadfruit, in addition to nuts) and a variety of marine resources, including reef and pelagic fish. The stable isotope results indicate that wealthy individuals and males were eating more foods from higher trophic levels, interpreted as being high status animal foods. The socially differentiated food consumption patterns are discussed within a Pacific island context. Am J Phys Anthropol 151:589–603, 2013. © 2013 Wiley Periodicals, Inc.